Distributed optimization based on improved push-sum framework for optimization problem with multiple local constraints and its application in smart grid - Xu, Qian; Yu, Chutian; Yuan, Xiang; Wei, Mengli; Liu, Hongzhe (Frontiers of information technology & electronic engineering, 2023)
In this paper, the optimization problem subject to N nonidentical closed convex set constraints is studied. The aim is to design a corresponding distributed optimization algorithm over the fixed unbalanced graph to solve the considered problem. To this end, with the push-sum framework improved, the distributed optimization algorithm is newly designed, and its strict convergence analysis is given under the assumption that the involved graph is strongly connected. Finally, simulation results support the good performance of the proposed algorithm.